COMPARATIVE EVALUATION OF CONVENTIONAL VERSUS RAPID METHODS FOR AMPLIFIABLE GENOMIC DNA ISOLATION OF CULTURED Azospirillum sp. JG3 - Stalis Norma Ethica; Dilin Rahayu Nataningtyas; Puji Lestari; Istini Istini; Endang Semiarti; Jaka Widada; Tri Joko Raharjo (Universitas Gadjah Mada, 2013)
As an initial attempt to reveal genetic information of Azospirillum sp. JG3 strain, which is still absence despite of the strains' ability in producing valued enzymes, two groups of conventional methods: lysis-enzyme and column-kit; and two rapid methods: thermal disruption and intact colony were evaluated. The aim is to determine the most practical method for obtaining high-grade PCR product using degenerate primers as part of routine-basis protocols for studying the molecular genetics of the Azospirillal bacteria. The evaluation includes the assessment of electrophoresis gel visualization, pellet appearance, preparation time, and PCR result of extracted genomic DNA from each method. Our results confirmed that the conventional methods were more superior to the rapid methods in generating genomic DNA isolates visible on electrophoresis gel. However, modification made in the previously developed DNA isolation protocol giving the simplest and most rapid method of all methods used in this study for extracting PCR-amplifiable DNA of Azospirillum sp. JG3. Intact bacterial cells (intact colony) loaded on electrophoresis gel could present genomic DNA band, but could not be completely amplified by PCR without thermal treatment. It can also be inferred from our result that the 3 to 5-min heating in dH2O step is critical for the pre-treatment of colony PCR of Azospirillal cells.